PALAEOGRAPHIC EVOLUTION OF PINDOS BASIN DURING PALEOGENE USING CALCAREOUS NANNOFOSSILS - Ananiadis, G.; Vakalas, I.; Zelilidis, A.; Stoykova, K. (Bulletin of the Geological Society of Greece, 2018)
A different basin evolution is suggested between the northern and southern parts of the Pindos basin, based on biostratigraphic dating results. Characteristic nannofossils showed that flysch sedimentation in the whole basin started in the Paleocene and generally finished during the Eocene, with the exception of the Konitsa and Milia areas where sedimentation lasted until Early Oligocene. Although, basin depth increased southwards, Kastaniotikos and Sperchios faults affected the geometry of Pindos basin, creating ridges and troughs within the basin. Due to this segmentation of the basin, the continuity of the sedimentation in the northern part of the study area until Oligocene is suggested. Calcareous nannofossils recovered from this northern part indicate a Paleocene NP5 to early Cligocene (NP20-21) age. On the other hand, in the southern part, sedimentation of flysch was lasted until middle Eocene. According this model, sedimentation in the southern part, stopped during the middle Eocene, was followed by subaerial exposure and the migration of clastic sedimentation to the western part of Pindos zones (Pindos foreland basin of Ionian zone). At this time, in the northern part, a small-restricted basin was continuously active as a piggyback basin from upper Eocene to lower Oligocene and shallow deposits (slope and submarine canyon deposits, delta fan deposits) accumulated.